The mandibular lingula's position in children as a reference to inferior alveolar nerve block - Kanno, Cláudia Misue [UNESP]; Oliveira, José Américo de [UNESP]; Cannon, Mark; Carvalho, Antonio Augusto Ferreira [UNESP] (My University, 2005)
Purpose: The objective of this study was to evaluate the position of the mandibular lingula (ML) to provide data for inferior alveolar nerve block techniques in children. Methods: One hundred fifty-four panoramic radiographs of 7- to 10-year-old boys and girls were analyzed. Measurements were taken from the ML to the occlusal plane, and the percentile distances of the ML to ramal borders were determined. Results: The distance between the ML and the occlusal plane showed a gradual increase, but only in the male group was it statistically significant. MLs ratio position on the ramus remained constant in all analyzed groups. In the 7-year-old group, the ML was observed above the occlusal plane in 70% of girls and 55% of boys. That percentage reached 85% of all children by age 10. Conclusions: The mandibular lingula's ratio position remained constant. Inferior alveolar anesthesia should be administered at least 6 mm above the occlusal plane in 7- to 8-year-old children, while 10 mm could be indicated for 9- to 10-year-old children. The mandibular lingula should be considered a reliable reference for further studies of inferior alveolar nerve block techniques.
Keywords: Anesthesia; Dental; Pediatric dentistry; analysis of variance; cephalometry; child; dental anesthesia; female; histology; human; male; mandible; mandibular nerve; methodology; nerve block; radiography; Analysis of Variance; Anesthesia, Dental; Cephalometry; Child; Female; Humans; Male; Mandible; Mandibular Nerve; Nerve Block